Assessment of olive wastes as energy source: pyrolysis, torrefaction and the key role of H loss in thermal breakdown. (15th March 2015) - Volpe, Roberto; Messineo, Antonio; Millan, Marcos; Volpe, Maurizio; Kandiyoti, Rafael
Abstract: The present work describes the first stage of a multi-stage process seeking to develop a usable and cheap design for a downdraft gasifier fed with lingo-cellulosic olive waste. The thermochemical behaviour of two types of olive waste has been assessed during pyrolysis and torrefaction experiments. Olive tree trimmings and olive pulp were pyrolysed in a quartz reactor at peak temperatures between 400 °C and 650 °C, during slow heating experiments (50 °C/min) under a helium blanket. These samples were also torrefied under nitrogen to temperatures between 200 °C and 325 °C. At the peak temperature of 650 °C, mass losses of up to 74% were recorded. Elemental analyses of the chars showed a consistent linear increase of Carbon to values around 75% and a linear decrease of oxygen to values near 10%. By contrast, the H-content remained relatively constant up to about 300 °C and then decreased to as the peak temperature was raised further. The results suggest that the combination of mass loss and H-content may be used as indicators for linear char-GCV increases up to the torrefaction limit of around 300 °C. Highlights: A process to develop a design for an olive waste downdraft gasifier is described. Thermochemical processes may be tracked by Hydrogen concentration in the chars. SEM micrograms reveal the precise stages by which the samples thermally decompose.